USE OF PRODUCTIVE ZAKAT IN LAZ AND BAZNAS IN JEMBER - Devirahtiasari Pratiwi (International Journal of Research Science and Management, 2019)
Productive zakat can improve welfare mustahiq if managed properly. There are three institutions that carry out productive zakat in Jember, namely the National Zakat Agency (Baznas), Lazismu and LAZ YDSF. LAZ carries out management functions in carrying out productive zakat, namely planning, implementation and supervision. But there are still obstacles in the implementation of productive zakat, namely in the process of supervision and the limited amount of funds. Actions that can be taken to overcome these obstacles include forming a special team to supervise and assist MSMEs in carrying out their business and publicizing the importance of zakat and the benefits of zakat for welfare.